Hirayama disease: An ayurvedic approach - Sukumar Ningappa Nandigoudar; Swarda Ravindra Uppin; Anita Dalawai; Namrata Bhagaje (Wolters Kluwer Medknow Publications, 2021)
Introduction: Hirayama disease, also known as Monomelic amyotrophy or benign focal amyotrophy, is a rare motor neuron disease. It is reported to primarily affect males of southeast Asia, particularly India and Japan. Clinical findings and Intervention: A 27 years male patient approached Ayurveda OPD with a known case of Hirayama Disease from last 9 years. Considering this condition, the treatment was planned according to Ayurvedic Medicinal system which included courses of Nasya karma, Basti karma and Shamana aushadi. Outcome: Post treatment, the patient showed considerable clinical improvement, and arrest in disease progression was observed. Conclusion: The present condition is understood under the spectrum of Vata vyadhi and was diagnosed as a case of Viswachi. The treatment was focused upon pacifying vata Dosha and restoring strength and functional capacity.